PHASE AQUILIBRIA IN WATER-GELATIN-LOCUST BEAN GUM SYSTEM - Antonov, Yurij A; Gonçalves, M P (Journal of characterization and development of novel materials, 2018)
Thermodynamic compatibility and phase equilibria in aqueous systems containing locust bean gum (LBG) and acid or alkaline gelatin samples with similar molecular weights (~100 kDa), but different isoelectric points (7.9 and 4.9 respectively) were studied. The effects of the state of gelatin molecules [molecular-dispersed and colloidaldispersed (~0.4 pm)] and limited degradation of biopolymers on their incompatibility are investigated. Passing from partially degraded to molecular-dispersed and then to colloidal-dispersed gelatins results in a decrease of the total concentration in the threshold point (C·t), and in increasing asymmetry of phase diagrams. Compatibility of LBG with gelatins is minimal at low ionic strength (p) and pH close to their isoelectric points. In the two-phase region, the degree of compatibility, determined by the phase diagrams, was dependent on pH and ionic strength of mixtures, as well as on ionogenic properties of the gelatins studied, varying according to the change of gelatin-solvent interaction.